The psychological impact of diagnosis of sinonasal, nasopharyngeal, and laryngeal cancers: a systematic review - Bonafede, Michela; d'Errico, Angelo; Rugarli, Sabrina; Mensi, Carolina; Miligi, Lucia; Calisti, Roberto; della Gatta, Rosa; Piro, Sara; Melis, Paola; Vasselli, Donatella; Binazzi, Alessandra (Frontiers in Psychology, 2024)
Objective: High risk of degraded quality of life and psychological distress is observed in patients diagnosed with sinonasal, nasopharyngeal and laryngeal cancers which could be caused by exposure to carcinogens in the workplaces. This review was aimed to investigate the psychological impact of diagnosis associated with the possible occupational etiology of such neoplasms and to explore the instruments that evaluate the QoL, anxiety and depression in these patients. Methods: Studies were included if they described aspects of the psychological impact of the diagnosis of sinonasal, nasopharynx and larynx cancers and reported results distinguished by tumour site. The psychological impact was assessed as health-related quality of life (QoL), anxiety and depression, identified using reliable psychometric questionnaires at the time of diagnosis and one year later. Results: Out of more than 5,900 records identified, 442 studies fulfilled the eligibility criteria and 436 were excluded after full-text screening, resulting in 6 studies to be included in the review. The EORTC QLQ-C30, EORTC QLQ-H&N35 and FACT were used to evaluate the QoL, whereas the HADS and CES-D questionnaires employed to assess anxiety and depression. QoL scores were similar to those of the general population at the time of diagnosis and unchanging or slightly improving at one year since diagnosis. In contrast, a higher prevalence of anxiety and depression compared with the general population was observed, although results were inconsistent across the very few studies identified. No study investigating the relationship between the potential occupational aetiology and QoL or distress was found. Conclusions: Exploring the existing scientific literature on emotional distress in sinonasal, nasopharyngeal and laryngeal cancer patients was motivated by the disfiguring nature of treatment and the further emotional burden due to their occupational aetiology. Unfortunately, such a crucial element was neither examined in any study, as well as other risk factors (lifestyle, smoking, drinking, etc.). Patients’ employment history should be considered, to assess the possible impact of believing to be affected by an occupational disease in the evaluation of their psychological distress. This would support evidence‐based recommendations about dedicated psychological interventions.